2006
DOI: 10.1203/01.pdr.0000238250.64591.44
|View full text |Cite
|
Sign up to set email alerts
|

The G Protein-Coupled Receptor Kinase 4 Gene Modulates Stress-Induced Sodium Excretion in Black Normotensive Adolescents

Abstract: Approximately 20 -40% of adolescents have shown a reduction of urinary sodium excretion (U Na V) in response to blood pressure (BP) increase during behavioral stress. G protein-coupled receptor kinase 4 (GRK4) mediates the pressure and natriuresis relation. The present study investigated the impact of GRK4 genetic variants on U Na V under stress. A total of 664 normotensive adolescents including whites and blacks (17.6 Ϯ 3.3 yrs, 43.4% blacks) were recruited. Participants were subjected to a stress-protocol in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 26 publications
(22 reference statements)
1
18
0
Order By: Relevance
“…Transgenic mice expressing human GRK4γ 486 V are normotensive on a normal-salt diet and become hypertensive on a high-salt diet [90•]. Transgenic mice expressing human GRK4γ 65 L are normotensive on both normal and high salt intake, but in African American adolescent males carrying this variant, mental stress increases blood pressure and decreases sodium excretion [99]. Salt-sensitive hypertensive Japanese patients carrying at least three GRK4 gene variants have an impaired natriuretic response to a dopaminergic drug [100].…”
Section: Role Of G Protein-coupled Receptor Kinasesmentioning
confidence: 99%
“…Transgenic mice expressing human GRK4γ 486 V are normotensive on a normal-salt diet and become hypertensive on a high-salt diet [90•]. Transgenic mice expressing human GRK4γ 65 L are normotensive on both normal and high salt intake, but in African American adolescent males carrying this variant, mental stress increases blood pressure and decreases sodium excretion [99]. Salt-sensitive hypertensive Japanese patients carrying at least three GRK4 gene variants have an impaired natriuretic response to a dopaminergic drug [100].…”
Section: Role Of G Protein-coupled Receptor Kinasesmentioning
confidence: 99%
“…The GRK4 locus on human chromosome 4p16.3 is linked with hypertension [88][89][90][91]. The increase in BP with age in white and African Americans is associated with GRK4 65L [92] and the increase in BP and decrease in sodium excretion with mental stress is associated with GRK4 65L in adolescent African Americans [93]. GRK4 486V, by itself [82] or in conjunction with GRK4 65L and GRK4 142V [83], is associated with salt sensitivity.…”
Section: Impaired Renal D 1 Receptor and Hypertensionmentioning
confidence: 99%
“…16 The R65L aminoacid substitution was also associated with impaired stress-induced sodium excretion in Black normotensive men. 17 In a preliminary unpublished study in South Africans, we found the variant T allele of the A142V SNP to be significantly more frequent in Blacks compared with Whites (73 vs 23%, respectively) (Rayner et al, unpublished data). With this in mind we decided to study the effects of the A142V and R65L SNPs on the BP response to dietary intervention in the study performed previously.…”
Section: Introductionmentioning
confidence: 91%